Stigma in financial market: Evidence from liquidity auctions and discount window borrowing during the crisis - Olivier Armantier; Eric Ghysels; Asani Sarkar; Jeffrey Shrader (Federal Reserve Bank of New York, 2011)
We provide empirical evidence for the existence, magnitude, and economic impact of stigma associated with banks borrowing from the Federal Reserve's discount window facility. We find that, during the height of the financial crisis, banks were willing to pay an average premium of at least 37 basis points (and 150 basis points after Lehman's bankruptcy) to borrow from the Term Auction Facility rather than from the discount window. The incidence of stigma varied according to bank characteristics and market conditions. Finally, we find that discount window stigma is economically relevant since it increased banks' borrowing costs during the crisis. Our results have important implications for the provision of liquidity by central banks.
Keywords: G01; G28; G21; G12; 330; discount window; Term Auction Facility; stigma; crisis; monetary policy